2010
DOI: 10.1590/s1516-89132010000200028
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of erythrosin B dye by paramorphic Neurospora crassa 74A

Abstract: The present work used paramorphic forms of Neurospora crassa 74A to remove erythrosine. The fungus culture was grown in medium containing the dye, as only carbon source for 2 and 90 h of interaction. A washing process using distilled water isolated the cellular mass mycelia was dried for 12 h at 105ºC and transformed in fine powder and analyzed in FTIR. The supernatant was analyzed through spectrophotometer UV-Vis and FTIR. Significant differences in the spectrum of UV-VIS and FTIR were observed between the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The genus Neurospora has also been the target of biodegradation studies. According to de Jesus et al (2010), the cultivation of this fungus in the presence of the commercial dye Erythrosine (an organoiodine compound containing 4 iodine groups used as a red food colorant) suggested the possibility of the enzymatic action of laccase in the biodegradation of this xenobiotic compound.…”
Section: Growth Inhibition Testsmentioning
confidence: 99%
“…The genus Neurospora has also been the target of biodegradation studies. According to de Jesus et al (2010), the cultivation of this fungus in the presence of the commercial dye Erythrosine (an organoiodine compound containing 4 iodine groups used as a red food colorant) suggested the possibility of the enzymatic action of laccase in the biodegradation of this xenobiotic compound.…”
Section: Growth Inhibition Testsmentioning
confidence: 99%
“…Only one work on Ery B biodegradation is available (Pereira et al 2009). Jesus et al (2010) results on dye removal by the fungus Neurospora crassa 74A suggested the possibility of biodegradation in proportion to the contact time between the dye and the fungal biomass. Itoh and Yatome (2004) have reported the aerobic biodegradation of six other xanthene dyes also by a white rot fungus, Coriolus versicolor, but as compared to our results with anaerobic bacterial biomass, where color removal occurred in few hours, their process took some days.…”
Section: Dye Biodegradationmentioning
confidence: 99%
“…Xanthene represent a distinct class of dyes that are use in food, cosmetics, paper, and ink, due to superior dyeing and coloring properties, but have poor biodegradability and some of them are toxic (Itoh and Yatome 2004). Only six reports on enzymatic oxidation of xanthene dyes are available (Itoh and Yatome 2004;Jesus et al 2010) and any about enzymatic reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Other effects are associated with bronchoconstriction, sequential vascular response, elevation of protein-bound iodide, and chromosomal damage. In spite of these concerns, the fate of Erythosine B in the environment is less investigated, and there is a limited number of published data on its removal from aqueous effluents which contain dissolved erythrosine, difficult to be eliminated by conventional wastewater treatments [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%